Giáo trình Côn trùng nông nghiệp - Trần, Đăng Hòa; Trần, Thị Hoàng Đông; Nguyễn, Thị Giang; Lê, Khắc Phúc (Đại học Huế, 2017)
.
Keywords: BẢO VỆ THỰC VẬT; BẢO VỆ THỰC VẬT - Côn trùng nông nghiệp - Giáo trình